Manifestation of Surah Al-Ma’un in the Value of Barakah as the Ethical Foundation for CSR Program Development at CV. Adnan Tour and Travel - Ghaliyah Nimassiita Triseptya; Alimuddin Alimuddin; Syarifuddin Syarifuddin (Universitas Hamzanwadi, 2025)
This study examines how the values of Surah Al-Ma’un are manifested within the concept of barakah (divine blessings) and how these values serve as an ethical–spiritual foundation for designing Corporate Social Responsibility (CSR) programs at CV. Adnan Tour. Surah Al-Ma’un highlights social compassion, justice, empathy, and moral accountability as intrinsic expressions of Islamic religiosity. Employing a phenomenological approach, this research explores the lived experiences of business owners and employees in interpreting the meaning of barakah and its operationalization in the company’s CSR initiatives. The findings reveal that Surah Al-Ma’un nurtures a moral consciousness that corporate profit inherently contains the rights of others; hence, it must be redistributed through almsgiving, social assistance, and community-beneficial programs such as the “Friday Blessings Program” and Qur’an distribution to local mosques. Barakah is perceived not merely as material gain but also as business tranquility, protection from risks, a positive organizational climate, and enhanced customer trust. The values of Al-Ma’un also cultivate a culture of empathy, honesty, and social care, strengthening the company’s public reputation. Thus, the Al-Ma’un–based CSR model at CV. Adnan Tour goes beyond regulatory compliance and becomes a meaningful form of spiritual value internalization fostering business sustainability and social welfare.